(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research delves into Ahmednagar district, a drought-prone region in Maharashtra, to investigate the spatial distribution and impact of farm ponds on agricultural development, water resources. The primary aim is to assess the role of farm ponds in alleviating water scarcity for crops and their influence on the net irrigated area. Conducting field surveys, questionnaires, and interviews, the study gathers primary data on farm pond characteristics. Among approximately 9798 farm ponds constructed from 2005 to 2015, a 10% sample is analyzed to comprehend their role in agricultural development. Statistical analysis reveals that farm ponds serve as vital irrigation tools, ensuring a reliable water source and contributing to increased crop production. Spatial distribution analysis categorizes tehsils into various density levels, with Rahata, Nagar, and Karjat showing notably high densities. The proportion of irrigated area by farm ponds relative to Net Irrigated Area (NIA) at different levels, the study unveils an average proportion of 50.53%, with a standard deviation of 19.33%. These findings underscore the substantial impact of farm ponds on agricultural productivity and water security in the region. The abstract highlights farm ponds as crucial solutions to water scarcity challenges, offering valuable insights for policymakers and agricultural extension workers to implement sustainable water resource management strategies in drought-prone areas.